AD, Volume 43, n° 1, 2018 - Full Issue - journal system, journal system (Africa Development, 2018)
Contents Editorial: (Re)making bodies – The structures and Dynamics of Aesthetics and Aspirations in an Evolving Africa ................1 Éditorial : Les transformations corporelles – structures et dynamiques d’esthétique et aspirations dans une Afrique en évolution .............3 Making Fashion, Forming Bodies and Persons in Urban Senegal Kristin Kastner....................................5 De la célébration à la profanation : le corps féminin dans la littérature africaine francophone Alioune Diaw......................21 Reinterpretation of “Traditional” Bodily Modifications by Young People in Contemporary Zimbabwe Hellen Venganai.............................43 Mémoires ancrées dans les corps noirs entre l’Afrique et le Brésil Maria Antonieta Antonacci...................61 The Gendered and Commodified Female Body in Contemporary Nigerian Fiction Sule Emmanuel Egya........................75 Using Transnational Soap Operas to Redefine Beauty in Cameroon Delphine Gwanvalla Ngehndab.............................91 “The (Re)Making of Bodies and Enforcement of Masculinities: Aesthetics and Aspiration at a Zimbabwean University” Pedzisayi Leslie Mangezvo.............................113 Construction sociale du corps de l’accouchée chez les Ébrié : une dynamique entre traditionalisme et modernisme Francis A. Adiko, Léopold Y. Yao & Bassirou Bonfoh.........................127 The Stars Must Shine: Nollywood Talent Scouts’ Influence on Theatre Arts Students’ Body Image in Nigerian Universities Adediran Daniel Ikuomola.........................139